2009
DOI: 10.1080/09638180802681511
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Logics, ICT and Stability of Management Accounting

Abstract: The purpose of this paper is to study the institutional logics of how and why two case units in the Finnish Defence Forces have reacted differently to external pressures originating from the State Audit Office to change their management accounting systems. The situation is made complex due to the fact that in military organisations, accountants' tasks have traditionally consisted of bookkeeping and financial reporting, while management accounting tasks especially (e.g. planning and control) have been performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 48 publications
3
93
0
8
Order By: Relevance
“…The concept of institutional logic has received increasing attention in accounting studies (Thornton, 2004; Lounsbury, 2008; Hyvönen et al, 2009; Reay and Hinings, 2009; and ter Bogt and Scapens, 2009). Institutional logic is a common guiding decision‐making principle for most organizational actors (see Lounsbury, 2008; and ter Bogt and Scapens, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of institutional logic has received increasing attention in accounting studies (Thornton, 2004; Lounsbury, 2008; Hyvönen et al, 2009; Reay and Hinings, 2009; and ter Bogt and Scapens, 2009). Institutional logic is a common guiding decision‐making principle for most organizational actors (see Lounsbury, 2008; and ter Bogt and Scapens, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The different organizational responses to institutional pressures (Oliver, 1991) allow performance measurement systems (PMSs) to be used in different ways in organizations. Moreover, PMSs confront varying organizational pressures, legitimations and logics in the public sector (Hyvönen et al, 2009; Rautiainen, 2010; and ter Bogt and Scapens, 2009). The resulting variation in PMS use can be called ‘practice variation’ (see Lounsbury, 2001 and 2008; and Johansson and Siverbo, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Further, there may be various professionally and organizationally developed institutional logics, i.e. specific decision-making principles, in the processes of selecting and using KPIs within organizations (see Hyvönen, Järvinen, Pellinen and Rahko, 2009;Lapsley, 2008;Modell, 2009;Reay and Hinings, 2009;Rautiainen and Järvenpää, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that different responses can occur even within a single public sector organisation, when it is large enough (Hyvonen et al, 2009). For example, actor-network theory can be used as a conceptual framework to analyse the adoption process.…”
Section: Discussionmentioning
confidence: 99%